2015
DOI: 10.3892/etm.2015.2557
|View full text |Cite
|
Sign up to set email alerts
|

Viral encephalitis complicated by acute retinal necrosis syndrome: A case report

Abstract: Abstract. Acute retinal necrosis syndrome (ARN) is a viral infection characterized by focal retinal necrosis. Viral meningitis complicated by ARN is relatively rare. In the present case study, a 44-year-old male presented with fever, headache and mental disorder. After four days, the patient developed blurred vision. The patient was diagnosed with viral encephalitis complicated by bilateral ARN, based on the examination results. After treatment with antivirals and systemic glucocorticoids, the symptoms of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Furthermore, viral encephalitis may be a risk factor for retinal necrosis. The mechanism of ARN has yet to be elucidated; however, it has been indicated that the virus may be transmitted via the brain-optic nerve axon-retina pathway (Gaynor et al, 2001;Liang et al, 2015). Also, it has been shown that after PRV infects the rat retina, the virus can invade the central nervous system via anterograde trans-synaptic spread through axons in the optic nerve and also perhaps via retrograde transport through the oculomotor nucleus that innervates the extraocular muscles of the eye (Rassnick et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, viral encephalitis may be a risk factor for retinal necrosis. The mechanism of ARN has yet to be elucidated; however, it has been indicated that the virus may be transmitted via the brain-optic nerve axon-retina pathway (Gaynor et al, 2001;Liang et al, 2015). Also, it has been shown that after PRV infects the rat retina, the virus can invade the central nervous system via anterograde trans-synaptic spread through axons in the optic nerve and also perhaps via retrograde transport through the oculomotor nucleus that innervates the extraocular muscles of the eye (Rassnick et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Although uncommon, other cases of ARN associated with HSV encephalitis have been reported. A search of English PubMed articles about patients diagnosed with both ARN and HSV-1 or HSV-2 encephalitis revealed 34 case reports that are summarised in table 1 8-35. Median age was 44.5 years (range of 23 days to 68 years old) and male gender was reported in 24/36 (67%) cases.…”
Section: Discussionmentioning
confidence: 99%
“…It can also cause acute retinal necrosis (ARN) that presents with uveitis, occlusive vasculitis and necrosis of the retina, ultimately leading to retinal detachment, optic nerve atrophy and severe vision loss 2. Previous studies report an incidence of 1 case per 1.6–2.0 million people, usually associated with viral encephalitis 3. There is an equal gender distribution of the disease and most cases occur between the fifth and seventh decades of life 4…”
Section: Introductionmentioning
confidence: 99%